VILLAGE DEVELOPMENT PROGRAM: THE VIEW OF "ASKESI ROS" IN SOCIAL CONSTRUCTION, A DEVELOPMENT REALITY OF LOCAL PAPUAN RESIDENTS IN MANOKWARI REGENCY - Triman Tapi , Ganjar Kurnia , Iwan Setiawan , Agus Sumule (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to explore the knowledge and experience of local Papuan on village programs, in accordance with the massive previous 10 years developmental budget. Data were obtained from three villages, using questionnaires, focus group discussions (FGD), observations, and interviews. The field findings added more knowledge and experience to participants, such as the program’s name, the amount of funds, and its source. The initial limited knowledge was due to the dominance of village elites in information mastering, social status, participation levels (Maseleno et al., 2019), language factors, and social relationships. Village development is internalized with the view of life "askesi ros" (progress), which is subjective, considers the development program as the domain and responsibility of the government. Furthermore, the local community tends to participate objectively, assuming the program provides direct added value. Conversely, the village elite felt they had the right to enjoy the "askesi ros" in order to accelerate program implementation, however, the community to limited to several developmental stages. The development program needs to start from the village because it is owned by the interest of the government (Monuh). This is because, for the past 10 years, the welfare of the poor population has been ignored with the program destroyed by various interests, minimal participation, and assistance. Therefore, the willingness and sincerity of the village elite, all program managers, and stakeholders are needed in appreciating the cultural value and meaning of "askesi ros" as a symbol used to represent "Ororoisa" development (flowing down).